Analisis Determinan Sektor Pariwisata Terhadap Pendapatan Asli Daerah Kabupaten/Kota di Provinsi Nusa Tenggara Timur - Kristian Adiputra Jelamu; I Wayan Priyana Agus Sudharma (Pusat Riset dan Inovasi Nasional, 2026)
East Nusa Tenggara (NTT) Province possesses tourism potential that is recognized both nationally and internationally. However, the actual contribution of this sector to local revenue (PAD) remains significantly lower compared to Bali and West Nusa Tenggara (NTB). This phenomenon indicates a gap between the existing potential and the optimization of the tourism sector. This study aims to analyze the simultaneous and partial effects of the number of tourist attractions, hotels, and restaurants on the local revenue of regencies/municipalities in East Nusa Tenggara Province. The study employs panel data consisting of cross-section and time-series data from 2016 to 2023. Data analysis was conducted using panel data regression with the assistance of Eviews-12 software. The findings reveal that the number of tourist attractions, hotels, and restaurants simultaneously exert a significant influence on local revenue (PAD) in regencies/municipalities of East Nusa Tenggara Province. Partially, the number of tourist attractions has a positive and significant effect on local revenue (PAD). Likewise, the number of hotel rooms shows a positive and significant effect on local revenue (PAD). Furthermore, the number of restaurants also has a positive and significant effect on local revenue (PAD) in regencies/municipalities across East Nusa Tenggara Province.